Dominant-negative effect of a missense variant in the TASK-2 (KCNK5) K+ channel associated with Balkan endemic nephropathy - Reed, Alan; Bucci, Giovanna; Abd-Wahab, Firdaus; Tucker, Stephen J. (PLOS, 2016)
TASK-2, a member of the Two-Pore Domain (K2P) subfamily of K+ channels, is encoded by the KCNK5 gene. The channel is expressed primarily in renal epithelial tissues and a poten- tially deleterious missense variant in KCNK5 has recently been shown to be prevalent amongst patients predisposed to the development of Balkan Endemic Nephropathy (BEN), a chronic tubulointerstitial renal disease of unknown etiology. In this study we show that this variant (T108P) results in a complete loss of channel function and is associated with a major reduction in TASK-2 channel subunits at the cell surface. Furthermore, these mutant subunits have a suppressive or ‘dominant-negative’ effect on channel function when coex- pressed with wild-type subunits. This missense variant is located at the extracellular surface of the M2 transmembrane helix and by using a combination of structural modelling and fur- ther functional analysis we also show that this highly-conserved threonine residue is critical for the correct function of other K2P channels. These results therefore provide further struc- tural and functional insights into the possible pathophysiological effects of this missense variant in TASK-2.